Identifikasi Pengaruh Constructed Wetland dalam Menurunkan Kandungan Mikroplastik Pada Air Lindi - Ichdatunnisa, Rania; Raden Kokoh Haryo Putro (Jurnal Serambi Engineering, 2025)
With the increasing use of various types of single-use plastics, plastic waste is piling up in landfills. The degradation process of plastic causes plastic waste to become small pieces, namely microplastics, which will be absorbed into leachate channels and disposed into the environment if not treated. The entry of microplastics into the ecosystem, especially in the food sources we consume, will have a harmful impact on human health, such as cancer, respiratory disorders, and more. Subsurface Flow Constructed Wetland (SSF-CW) treatment is used to reduce the microplastic content in leachate. Microplastics were found in every sample, but SSF-CW with plants resulted in a better reduction of microplastics than without plants, which was able to reduce 72% of the microplastics from the initial total in the influent. The forms of microplastics found were fibers and filaments, with fiber-shaped microplastics being the dominant form found. The sizes of the microplastics found in this study ranged from 5 mm - 0.1 mm, and in the two samples, most microplastics were found to be 0.5 mm - 0.1 mm. Thus, leachate treatment with constructed wetlands can reduce the microplastic content in leachate, and the plants play an active role in retention, physical filtration and adsorption of microplastics.